Pengaruh Kompetensi SDM, Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) dan Pengendalian Internal terhadap Kualitas Informasi Laporan Keuangan pada Kantor Pengadilan Agama Kabupaten Brebes - Navira Nur Hannisa; Dumadi Dumadi; Yenny Ernitawati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Poor quality of financial statements can have an impact on the inaccuracy of the information presented, thereby hindering data-based decision-making. This can also affect the accountability and transparency of financial management within government agencies. This study aims to investigate the influence of human resource (HR) competence, the implementation of the Agency-Level Financial Application System (SAKTI), and internal control on the quality of financial statement information at the Brebes Regency Religious Court Office. The research method used is quantitative with a survey approach. The research sample consists of employees who are directly involved in the financial reporting process. Data was collected through questionnaires and analyzed using regression methods to test the relationship between these variables. Human resource competence has a positive and significant effect on improving the Quality of Financial Statement Information at the Brebes Regency Religious Court office by 66.5%. The implementation of SAKTI had a positive and significant effect on improving the quality of financial statement information by 17.5%. Internal Control had a positive and significant effect on improving the Quality of Financial Statement Information by 14.0%. HR competence, SAKTI implementation, and Internal Control simultaneously affect the improvement of the quality of financial statement information at the Brebes Regency Religious Court office. The variables of HR competence, SAKTI implementation, and internal control contributed 66.4% to the quality of financial statement information at the Brebes Regency Religious Court office, while the remaining 33,760% were influenced by variables that were not studied.